Modelling of titanium oxynitride films for decorative coating by using response surface methodology - Chanawee Sattha; Rachsak Sakdanuphab; Cittra Kedkaew; Aparporn Sakulkalavek (My University, 2019)
Abstract In this work, titanium oxynitride films were deposited on SS316L and Si-wafer substrates using reactive DC magnetron sputtering. An experimental design and statistical analysis were applied for the thin film coating. The experiment software (Design-Expert Software) was used to design the deposition parameters, including the plasma current density (10-25 mA/cm 2 ) and N 2 gas flow rate (20–60 sccm) by maintaining O2 gas flow rate. Response surface methodology based on a central composite design was used to empirically model the influence of the plasma current density ( I ) and N 2 ( N ) flow rate on the CIE colour system of titanium oxynitride thin films. The model fitting equations for two colour channels (a* and b*) were obtained and represented by a* = –26.65 + 0.67N + 2.92I + 0.02 NI – 0.01 N 2 – 0.12 I 2 and b* = 4.83 – 1.05 N + 1.72 I – 0.02 NI + 0.02 N 2 – 0.03 I 2 . In addition, the effects of current density and N2 flow rate on the chemical composition of TiON films were investigated by X-ray photoelectron spectroscopy (XPS). The titanium 2p (Ti 2p ) spectra indicated that the TiON and TiO2 structures depended on the deposition parameters. Additionally, the increase in N2 flow rate and current density affected the increase of the TiN structure. Cytotoxicity was performed on the Ti sheet and the TiON film on SS316L by assessing the cellular response to L929 fibroblast cells. The result shows that the TiON film on SS316L exhibits good biocompatibility with the L929 fibroblast cells.
Keywords: Deposition; Metal and Thin Film Mechanics